Association of Cancer and the Risk of Developing Atrial Fibrillation: A Systematic Review and Meta-Analysis - Ming Yuan; Zhiwei Zhang; Gary Tse; Xiaojin Feng; Panagiotis Korantzopoulos; Konstantinos P. Letsas; Bryan P. Yan; William K. K. Wu; Huilai Zhang; Guangping Li; Tong Liu; Yunlong Xia (Cardiology Research and Practice)
Aims. Previous studies have demonstrated epidemiological evidence for an association between cancer and the development of new-onset atrial fibrillation (AF). However, these results have been conflicting. This systematic review and meta-analysis was conducted to examine the relationship between cancer and the risk of developing atrial fibrillation. Methods. PubMed and Web of Science were searched for publications examining the association between cancer and atrial fibrillation risk published until June 2017. Adjusted odds ratios (ORs) or hazard ratios (HRs) and 95% CI were extracted and pooled. Results. A total of five studies involving 5,889,234 subjects were included in this meta-analysis. Solid cancer patients are at higher risk developing atrial fibrillation compared to noncancer patients (OR 1.47, 95% CI 1.31 to 1.66, p<0.00001; I2 = 67%, p=0.02). The risk of atrial fibrillation was highest within 90 days of cancer diagnosis (OR 7.62, 95% CI 3.08 to 18.88, p<0.00001) and this risk diminished with time. Conclusions. The risk of AF was highest within 90 days of cancer diagnosis. We should take into account the increased risk of atrial fibrillation development and, after this, study the embolic risk and potential indication of oral anticoagulation.